The labor market in Canada, 2000-2016 - W. Craig Riddell (IZA World of Labor, 2018)
During the 2000–2016 period, Canada's economy and labor market performed well. An important element in this success was the strong resource boom that lasted from the late 1990s to 2014. Since that time the economy and labor market have been undergoing a painful adjustment, a process that is now essentially complete. A good rule of thumb when examining many aspects of the labor market, such as the extent of unionization and the level of the minimum wage relative to the median wage, is that Canada is situated roughly halfway between the US and Europe.
Keywords: E24; J6; D6; 330; unemployment; resource boom; income inequality; Canada; job polarization